Characterization of merozoite-specific thrombospondin-related anonymous protein (MTRAP) in Plasmodium vivax and P. knowlesi parasites - Sy Thau, Nguyen; Nguyen, Tuyet-Kha; Truong, Nguyen Van; Chu, Thi-Thanh Hang; Na, Sung-Hun; Moon, Robert W.; Lau, Yee Ling; Nyunt, Myat Htut; Park, Won-Sun; Chun, Wan-Joo; Lu, Feng; Lee, Seong-Kyun; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Plasmodium vivax, the most widespread human malaria parasite, and P. knowlesi, an emerging Plasmodium that infects humans, are the phylogenetically closest malarial species that infect humans, which may induce cross-species reactivity across most co-endemic areas in Southeast Asia. The thrombospondin-related anonymous protein (TRAP) family is indispensable for motility and host cell invasion in the growth and development of Plasmodium parasites. The merozoite-specific TRAP (MTRAP), expressed in blood-stage merozoites, is supposed to be essential for human erythrocyte invasion. We aimed to characterize MTRAPs in blood-stage P. vivax and P. knowlesi parasites and ascertain their cross-species immunoreactivity. Recombinant P. vivax and P. knowlesi MTRAPs of full-length ectodomains were expressed in a mammalian expression system. The MTRAP-specific immunoglobulin G, obtained from immune animals, was used in an immunofluorescence assay for subcellular localization and invasion inhibitory activity in blood-stage parasites was determined. The cross-species humoral immune responses were analyzed in the sera of patients with P. vivax or P. knowlesi infections. The MTRAPs of P. vivax (PvMTRAP) and P. knowlesi (PkMTRAP) were localized on the rhoptry body of merozoites in blood-stage parasites. Both anti-PvMTRAP and anti-PkMTRAP antibodies inhibited erythrocyte invasion of blood-stage P. knowlesi parasites. The humoral immune response to PvMTRAP showed high immunogenicity, longevity, and cross-species immunoreactivity with P. knowlesi. MTRAPs are promising candidates for development of vaccines and therapeutics against vivax and knowlesi malaria.